2011
DOI: 10.1016/j.jhep.2011.01.040
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive risk assessment of mortality following donation after cardiac death liver transplant – An analysis of the national registry

Abstract: Background and Aims Organ scarcity has resulted in increased utilization of donation after cardiac death (DCD) donors. Prior analysis of patient survival following DCD liver transplantation has been restricted to single institution cohorts and a limited national experience. We compared the current national experience with DCD and DBD livers to better understand survival after transplantation. Methods We compared 1,113 DCD and 42,254 DBD recipients from the Scientific Registry of Transplant Recipients databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
131
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(137 citation statements)
references
References 16 publications
4
131
1
1
Order By: Relevance
“…There was no significant difference in the mean tumor number (P 5 1.00), TTV (P 5 0.44), or proportion with a TTV > 115 cm 3 (P 5 0.45) between HCC patients receiving DCD allografts (group 3) and HCC patients receiving DBD allografts (group 1). There was no significant difference in the mean AFP level before transplantation between HCC patients receiving DCD allografts and HCC patients receiving DBD allografts (P 5 0.61).…”
Section: Group 1 (Hcc-dbd) Versus Group 3 (Hcc-dcd)mentioning
confidence: 95%
See 2 more Smart Citations
“…There was no significant difference in the mean tumor number (P 5 1.00), TTV (P 5 0.44), or proportion with a TTV > 115 cm 3 (P 5 0.45) between HCC patients receiving DCD allografts (group 3) and HCC patients receiving DBD allografts (group 1). There was no significant difference in the mean AFP level before transplantation between HCC patients receiving DCD allografts and HCC patients receiving DBD allografts (P 5 0.61).…”
Section: Group 1 (Hcc-dbd) Versus Group 3 (Hcc-dcd)mentioning
confidence: 95%
“…The total tumor volume (TTV) was calculated by the addition of the volumes of each HCC [(4/ 3)pr 3 ], which were based on the maximum radiological radius of each tumor. For some analyses, previously published endpoints-TTV 115 cm 3 and AFP level 400 ng/mL-were used. 17,18 Pretransplant treatments of HCC were recorded if they occurred at any time between listing and transplantation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The advent of DCD lung donation has resulted in a 28% increase in transplant numbers in Australia with outcomes comparable to those from NDD donors (5). Livers, however, appear more sensitive to the effects of warm ischemia, with increasing rates of ischemic biliary strictures and worse survival following DCD liver transplantation (6,7). Similar concerns regarding the impact of warm ischemia and irreversible ischemic injury have thus far precluded the use of DCD hearts as cardiac allografts.…”
Section: Introductionmentioning
confidence: 99%
“…Donation after cardiac death (DCD) liver allografts have been pursued as one option to address the growing discordance between organ supply and demand by increasing the pool of available organs. Previous reports have demonstrated that proportionately DCD livers are used more frequently than donation after brain death (DBD) livers in patients with HCC (20.2% vs. 13%) (4,5). This is likely due to increasing tendency to use extended criteria organs in recipients with lower biological Model for End-Stage Liver Disease (MELD) scores because of the perception that these recipients are better able to tolerate an extended criteria organ (6).…”
Section: Introductionmentioning
confidence: 99%